Cross-cultural explorations - Goldstein, Susan B., author.
1 online resource
Keywords: "The fourth edition of Teaching Culture and Psychology (previously Cross-Cultural Explorations) provides an array of carefully designed instructor resources and student activities that support the construction and implementation of courses on culture and psychology. Revised and expanded from previous editions, the book enables instructors to use selected activities appropriate for their course structure. Part 1 explores a variety of pedagogical challenges involved in teaching about culture and psychology and details specific strategies for addressing these challenges. Part 2 (instructor resources) and Part 3 (student handouts) center around 90 activities designed to encourage students to think critically about the role of culture in a wide range of psychology content areas. These activities are based on current and classic cross-cultural research and take the form of case studies, self-administered scales, mini-experiments, database search assignments, and the collection of content-analytic, observational, and interview data. For each activity, instructors are provided with a lecture/discussion module as well as suggestions for variations and expanded writing assignments. Student handouts are available in this text as well on the Routledge website as fillable forms. Contributing to the inclusion of cultural perspectives in the psychology curriculum, this wide-ranging book enables instructors to provide students with hands-on experiences that facilitate the understanding and application of major concepts and principles in the study of culture and psychology, making it ideal for cultural psychology, anthropology, sociology, and related courses"--